ASSESSMENT OF METEOROLOGICAL DROUGHT SEVERITY IN THE FORMER HA GIANG PROVINCE, NORTHERN VIETNAM - Van Vu, Vuong; Luu Thu Thuy, Hoang; Trong Hoang, Vo; Thi Mui, Tran; Thi Cuc, Pham; Phuc Tuan, ong; Thi Thu Hien, Le; Thanh Binh, Nguyen; M. Manschadi, Ahmad; Xuan Hoang, Tran (HNUE Journal of Science: Journal of Natural Sciences, 2025)
The former Ha Giang Province in Northeastern Vietnam, characterized by complex mountainous terrain and climatic variability, is prone to drought. This study assesses meteorological drought severity using the aridity index (K) and monthly drought frequency (P), derived from meteorological data (1960–2024) collected at 18 meteorological, hydrological, and rainfall stations across the study area. Results show that monthly K values ranged from 0.1 to 3.1, peaking in February, while annual averages ranged from 0.1 to 0.5. Based on P, drought severity was classified into three levels: mild, moderate, and severe, with the highest frequencies in December and April. These findings provide a scientific basis to support disaster prevention and drought mitigation efforts in the region.